USULAN PERBAIKAN WAKTU PROSES PRODUKSI MENGGUNAKAN METODE 5S, VALUE STREAM MAPPING, DAN PROCESS ACTIVITY MAPPING PADA UD NOK SUSI - Mahendra, Aji; Susetyo, Joko; Wibowo, Agus Hindarto (Jurnal Rekavasi, 2023)
UD NOK SUSI is a business unit that produces rope, the purpose of this research is to implement 5S culture and reduce waste. Waste that arises from the remains of raw materials that have accumulated in production narrows the space for the production process and workers who make excessive movements often place tools/items haphazardly. 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) to reduce waste. Stage Seiri (Brief) is an activity to separate equipment that is not needed. Stage seiton (Neat) is an activity to store goods that are fixed and so that goods are neatly arranged. The seiso (Rehearsal) stage aims to maintain cleanliness in the work environment. The seiketsu (Treat) stage is to continue carrying out activities in the form of sorting, cleaning and arranging the development of positive habits in the workplace. The shitsuke (Diligent) stage aims to get used to the 5S culture. Solutions to reduce waste can also be analyzed using value stream mapping to describe the flow of materials and information in the production process from raw materials to finished products. The VSM mapping results are used to map the PAM. Process activity mapping to map all activities in detail in order to reduce waste. Reduced wastage. sorting process, namely: untying, separating. Small spinning namely: preparing the small mill, moving the pellets. Big spinning, namely: pulling the rope, preparing the reel tool, taking the big spinning rope. Finishing namely: attaching labels. The cycle time obtained was 398.80 minutes which was previously 419.44 minutes